Effects of co-exposure to copper and humic acids on microalga Chlorella vulgaris: growth inhibition, oxidative stress, and extracellular secretion. Issue 1 (1st January 2021) - Shi, Zhiqiang; Xu, Huacheng; Wang, Zhiyuan; Du, Haiyan; Fu, Xiaowei
ABSTRACT: Heavy metals were typical contaminants in aquatic ecosystems, while their effects on the biotoxicity and metabolism of algal cells in the presence of organic ligands were still unclear. In this study, the contrasting effects of Cu and humic acids (HA) on the growth inhibition, oxidative stress and extracellular secretion of microalga Chlorella vulgaris were studied at environmentally relevant concentrations of Cu (0~2 mg/L) and HA (0~20 mg/L). Results showed that, with increased Cu addition, the algal growth rate decreased while concentrations of superoxide dismutase and malondialdehyde increased showing evident growth inhibition and oxidative damage in the sole presence of Cu. However, the presence of HA could significantly alleviate the Cu-induced toxicity damage, and higher concentrations of HA exhibited greater alleviation efficiencies. Fluorescence spectroscopy combined with flow field flow fractionation revealed that secretion of 50 kDa~0.45 μm of extracellular protein-like substances was the critical fractions responsible for the biotoxicity alleviation. Analysis of Cu contents within extracellular polymeric substance (EPS) matrix showed that not only the secretion amounts but also the acquisition capacities of EPS matrix decreased due to the addition of HA. This study benefited an in-depth understanding toward the toxicity of heavy metals to aquatic microorganisms in natural waters that contained abundant organic ligands.